Muscarinic receptors - Christopoulos, Arthur; Nathanson, Neil M.; Fryer, Allison D. (Handbook of Experimental Pharmacology, 2012)
Muscarinic acetylcholine receptors have played a key role in the advancement of knowledge of pharmacology and neurotransmission since the inception of studies in these fields, and the effects of naturally occurring drugs acting on muscarinic receptors were known and exploited for both therapeutic and non-therapeutic purposes for hundreds of years before the existence of the receptors themselves was recognized. This volume presents a broad yet detailed review of current knowledge of muscarinic receptors that will be valuable both to long-time muscarinic investigators and to those new to the field. It describes the detailed insights that have been obtained on the structure, function, and cell biology of muscarinic receptors. This volume also describes physiological analyses of muscarinic receptors and their roles in regulating the function of the brain and of a variety of peripheral tissues. This volume shows how the study of muscarinic receptors continues to provide new and surprising insights not just to the cholinergic system but to the broad areas of neurobiology, cell biology, pharmacology, and therapeutics.